THE ETHOS OF TOLERANCE OF DIVERSITY IN POST-APARTHEID JURISPRUDENCE - Felix Dube (Obiter, 2022)
This article examines the South African judiciary’s understanding, interpretation, and application of the ethos of tolerance of diversity. The case law analysis shows that the courts treat tolerance of diversity as a constitutional value that derives from the Preamble and founding values of the Constitution of the Republic of South Africa, 1996. It also reveals that the courts moreover deduce the ethos of tolerance of diversity from the Bill of Rights, which entrenches rights and protects freedoms that could be classified as the building blocks of tolerance and diversity. Four major themes emerge from the analysis of the judiciary’s conceptualisation of the ethos of tolerance of diversity. These are the principles of reasonable accommodation; the right to be different; racial sensitivity; and transformation.